Bilateral distal femoral trochlear block migration after medial patellar luxation surgery in a dog - Danielle M. McNabney; Soroush Irandoust; Kenneth Bruecker; Peter Muir (Veterinary Research Communications, 2026)
The objective of this study was to describe management of a 2-year-old neutered male mixed breed dog with bilateral trochlear block recession migration with unilateral revision surgery. This is a rarely reported complication of a common surgical procedure. A 3D model segmented from a computed tomography scan using Mimics was performed before surgery to help determine whether surgical reduction of the osteochondral trochlear block fragments was feasible and preoperative press fit was acceptable. Subsequently, the trochlear block fragment in the left stifle was surgically reduced. During surgery, the osteochondral fragment was maintained in reduction with a transcondylar Kirschner wire because of imperfect press fit. The right stifle with trochlear block migration was treated medically. Short-term follow-up examination at 5 and 8 weeks revealed improvement in lameness after surgery. 3D modeling was also used to investigate potential underlying causes for bilateral block recession migration which was determined to be multi-factorial with excessive sulcoplasty depth being an important reason promoting risk of migration. During planning for femoral trochlear block recession sulcoplasty, it is important for the cut to be deep enough to help minimize risk of reluxation of the patella. However, press-fit of the osteochondral fragment is impaired when the depth of the recession sulcoplasty is excessive.

A provably stable numerical method for the anisotropic diffusion equation in confined magnetic fields - Dean Muir; Kenneth Duru; Matthew Hole; Stuart Hudson (Computer Physics Communications, 2025)

Growth responses of mixotrophic giant clams on nearshore turbid coral reefs - Kimberley Mills; Eleanor H. John; Duncan D. Muir; Nadiezhda Santodomingo; Kenneth G. Johnson; Muhammad Ali Syed Hussein; Sindia Sosdian (Coral Reefs, 2023)
Increasing evidence suggests that nearshore turbid coral reefs may mitigate bleaching of reef building calcifiers and play a critical role in the future of marine biodiversity in coastal areas. However, biomineralization processes on turbid reefs are relatively understudied compared to clear water counterparts and most published work focuses on corals. Here, we investigate how the mixotrophic giant clam Tridacna squamosa , a bivalve with ecological, cultural and economic significance, grows across a mosaic of less turbid to turbid reefs in the Coral Triangle. We construct growth chronologies from live and dead collected shells by measuring daily growth increments with petrography and scanning electron microscopy (SEM) to gain insight into growth rate on daily, seasonal and annual scales. We find annual growth is not significantly different across a turbidity gradient when scaled to ontogeny, while seasonal growth highly varies. K d (490) (a measurement positively correlated with turbidity) and chlorophyll- a are likely important factors driving seasonal growth on a turbid reef near a river, compared to sea surface temperature (SST), cloud cover and rainfall on a less turbid reef. On a daily scale, we investigate increment microstructure and spectral characteristics of chronologies, finding a relationship between tidal range and daily increments. Overall, our results indicate that light-enhanced calcification is likely most important in the less turbid reef, compared to heterotrophic feeding in the turbid reef. The trophic plasticity of T. squamosa may allow for its sustained growth in marginal conditions, supporting evidence that these habitats serve as important conservation hotspots for diverse reef building taxa.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Review of non-clinical risk models to aid prevention of breast cancer - Kawthar Al-Ajmi; Artitaya Lophatananon; Martin Yuille; William Ollier; Kenneth R. Muir (Cancer Causes & Control, 2018)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)